(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The global economy is facing significant challenges related to food scarcity, water scarcity, reduced land availability, and climate change. These challenges necessitate innovative approaches in agriculture to ensure sustainable food production and environmental stewardship. Electro-culture is a technique that uses high voltage electrostatic fields to improve seed germination and crop growth. Electro-culture has emerged as a promising approach for promoting plant growth without relying on chemical interventions. This study aims to evaluate the impact of a high voltage electrostatic field (20 kV) on the germination and growth of Cicer Arietinum (Bengal Gram). Germination booster plates are used to create a uniform field of 5 kV/cm having a gap of 4 cm. Experimental results demonstrated that the treatment of seeds using 20 kV for 120 seconds yielded superior outcomes compared to the treatment of 20 kV for 240 seconds. These findings highlight the potential of high voltage treatments to enhance seed germination and crop growth in Bengal Gram, offering a sustainable, efficient, and adaptable approach to agricultural practices, addressing environmental concerns, enhancing productivity, and promoting resource efficiency.